Diseño de una propuesta de valor para el fortalecimiento empresarial del Centro de Idiomas English Vision (Education for Life SAS) como aliado estratégico del sector BPO en la Región Caribe Colombiana (2024)
This innovation project applied the Design Thinking methodology to address the challenge of how a traditional English academy can penetrate the SME niche of the Colombian BPO (Business Process Outsourcing) sector with a B2B (Business to Business) service for preparing qualified personnel in language proficiency and soft skills. A value proposition was developed through ideation and prototyping sessions. Finally, the critical hypothesis was tested, obtaining positive acceptance that validated the relevance and value of the proposal for BPO companies. The value proposition designed indicated the possibility of enhancing its installed capacity to offer human capital specialized in customer service, technical assistance, and bilingual sales. These findings project an innovative solution with practical implications for the quality professional services outsourcing industry.